The Relationship Between Calling and Early Childhood Teacher Engagement: An Analysis of Generational Differences - Yulisinta, Florence; Sainstiani, Nurmeida; Pratiwi, Yulia (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
This study investigates the relationship between a sense of calling and work engagement among Early Childhood Education (ECE) teachers in Indonesia, underscoring the pivotal role of teachers in the educational transformation of the 21st century. A non-experimental, quantitative approach using correlational research methods was employed. Data were collected from 355 ECE teachers across Indonesia using the Early Childhood Teachers' Calling Scale (ECTCS) and the Utrecht Work Engagement Scale (UWES) to measure their sense of calling and work engagement, respectively. Spearman correlation, Mann–Whitney U, and Kruskal–Wallis tests were conducted for statistical analysis. The results showed a significant positive association between the sense of calling and work engagement among ECE teachers (r = 0.60, p < 0.0001). Specifically, higher levels of calling were associated with increased work engagement. The presence of family members in the teaching profession did not significantly affect teachers' sense of calling or work engagement (p = 0.07 > 0.05). The study revealed significant generational differences in calling and work engagement among ECE teachers, with notable variations across Generations X, Y, and Z. These findings contribute to understanding the factors influencing teachers' work engagement and highlight the importance of calling in educational settings. The results suggest that fostering a sense of calling could effectively enhance ECE teachers' work engagement, potentially improving educational outcomes and retention rates. However, the study's geographical focus on Indonesia may limit the generalizability of the findings to other cultural contexts. The results emphasize how intrinsic motivation shapes teacher engagement and commitment, suggesting implications for professional development and retention strategies. Future research should include longitudinal studies, broader geographic sampling, and investigations into interventions that strengthen teachers' sense of calling. This study contributes to the literature by emphasizing the role of intrinsic motivation in ECE teacher engagement, providing a foundation for future research in this critical educational domain.